HUBUNGAN MEKANISME KOPING DENGAN KUALITAS HIDUP PADA PASIEN TERMINAL DENGAN KANKER SERVIKS DI RSU. VINA ESTETICA MEDAN TAHUN 2016 - Elis Anggeria; Vesty Aprilian Daeli (Prodi Kesehatan Masyarakat Fakultas Kesehatan Masyarakat UIN Sumatera Utara, 2018)
ABSTRACT Coping mechanism is a way performed by individuals to adapt with stress. It is important to be performed to solve problems. The effective coping can assist individuals to get free from a long term stress. The objective of the study is to find out relationship between coping mechanism and patient quality of life of terminal patients of cervical cancer at Vina Estetika General Hospital Medan. This is a correlational study with cross-sectional design. The populations were 23 persons drawn by saturated sampling technique that 23 persons were determined to be the samples. The result of this study showed that 15 persons made a negative coping (65.2%) and 8 persons (34.8%) had a positive coping mechanism. Persons having a good quality of life were 6 persons (26.1%) and those having less quality of life were 17 persons (73.9%). Based on Spearman Correlation test with 2 tailed level of significance 0.00 (α < 0,05) with correlation coefficient of 0.760, it was found that there is a relationship between coping mechanism and patients quality of life of cervix cancer patients. The sufferers should be able to control their condition by positive coping strategy by having more focus on problems they face instead of emotions to reach better quality of life. Keywords: Coping Mechanism, Quality of Life, Cervix Cancer Patients